Digital Platforms for Integrated Rural Transformation in the TEKAD Program - Leroy Samy Uguy; Esther Kembauw; Maulida Nurfajrianti; Richard Evans (APTISI Transactions on Management (ATM), 2026)
Digitalization has become one of the foundational elements for the modernization of subsistence-based rural economies. The present study examines the implementation and performance of the Management Information System (MIS) and the Eastern Indonesia Gateway (EIG) in the Transformasi Ekonomi Kampung Terpadu (TEKAD) program. The study contributes by offering an integrated evaluative perspective that links digital governance, market visibility, fiscal latency, asynchronous processing, and visual pedagogy in rural transformation. Based on the 2025 Progress Report and 2021 Baseline Surveys over nine provinces in Eastern Indonesia, we describe how digital platforms enable evidence-based decision-making and market linkage. Based on statistical findings, the program has reached 101,920 households, representing 61.6% of the target beneficiaries. Despite this progress, several barriers remain, including a low budget absorption rate of 10.43%, which is largely associated with bureaucratic fiscal delays, limited literacy in remote districts such as Pegunungan Arfak, infrastructure gaps, and discontinuity in field-level facilitation, indicating that rural digitalization is constrained not only by technological limitations but also by fiscal latency and bureaucratic challenges nevertheless, the study highlights that rural digital platforms can support sustainable management, risk governance, financial transparency, and future fintech or blockchain-enabled accountability in village economic transformation, particularly when supported by asynchronous processing mechanisms that allow data to be stored locally and synchronized when connectivity becomes available, as well as visual teaching methods such as infographics, screen-based tutorials, and simplified digital training materials for village cadres.